Factors Related to the Needs of Parents Having School Age Thalassemic Children - Henny Suzana Mediani; Anita Tiara; Ai Mardhiyah (Faculty of Nursing Universitas Padjadjaran, 2019)
Thalassemia is a major genetic blood disorder that has negative impacts on thalassemic children and their family. The needs of parents while caring for thalassemia children are important matters because the failure of meeting needs of parents may affect their mental and physical health. Yet, litle is known about factors that meeting the needs of thalasemic child parents. The study aim was to identify factors that correlate with the needs of parents having a school age thalassemic child in west jave province. This research used correlational analytic with cross sectional approach. The population in this study were parents of school-age children with thalassemia major totaling 136 people using the total sampling method. Data were analyzed with bivariate using chi square and biserial points. Then a multivariate analysis used logistic regression. The results showed the age of parents related to information (p = 0.005) and professional (p = 0.004), parent gender related to information (p = 0,000), professional (p = 0.017), social (p = 0.035), financial (p = 0.023) and spiritual (p = 0.009). Parental education is related to information (p = 0,000), social (p = 0,005), emotional (p = 0,000), financial (p = 0,016) and spiritual (p = 0,001). Parent income is related to information (0,000), social (p = 0,006), emotional (p = 0,000), financial (p = 0,003) and spiritual (p = 0,004). The number of thalassemia major children is related to emotional (p = 0.015) and financial (p = 0.013). Parental needs are related to several factors. The importance of increasing the role of nurses as educators and consultants and helping parents find sources of spiritual, emotional and financial support for parents of school-age children with thalassemia.